2012
DOI: 10.1016/j.jrurstud.2012.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Ageing in changing community contexts: Cross-border perspectives from rural Ireland and Northern Ireland

Abstract: A B S T R A C TOngoing demographic, social, economic and cultural changes point to the dynamic and continually changing contexts of rural areas in Ireland and Northern Ireland. However, the influence of such changes on the lives of older people remains underexplored, particularly the question of how older people perceive, connect to and engage in their communities. Drawing on interviews and focus groups with indigenous and non-indigenous older people in three case-study sites in Ireland, Northern Ireland and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
88
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(89 citation statements)
references
References 42 publications
1
88
0
Order By: Relevance
“…As people age, they tend to spend more time at home and in their neighbourhoods (Gardner, 2011). Research in rural areas of Ireland (Walsh et al, 2012) found that older people depended on neighbours to be there when needed, as also evident in the findings of this study.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…As people age, they tend to spend more time at home and in their neighbourhoods (Gardner, 2011). Research in rural areas of Ireland (Walsh et al, 2012) found that older people depended on neighbours to be there when needed, as also evident in the findings of this study.…”
Section: Discussionsupporting
confidence: 80%
“…Research has shown that rural communities with high walkability are associated with independence and increased social interactions (Bacsu et al, 2014). Other studies have revealed difficulties accessing public transport services and the heavy reliance on owning a car, and being able to drive, as a barrier for older people living in rural environments to maintain friendships and keep in touch with significant others (Walker et al, 2013; Walsh, O’Shea, Scharf, & Murray, 2012). Social networks typically consist of family, friends and neighbours (Cornwell, Laumann, & Schumm, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the oldest old age group, 80 years and over, is estimated to triple by 2050 (United Nations 2013). While longevity is a positive reflection of advancements in medical science, public health practices and the economy, there is a tendency to problematise the ageing population fuelled by assumed ill-health and frailty that generates concerns regarding society's ability to support the needs of an ageing population (Powell 2010, Walsh et al 2012.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in 2013, 23 per cent of the rural population in Canada was over the age of 65 years compared to the national average of 13% (Keating et al 2013) and in Ireland, of those aged 65 years and over, 44% live in rural areas (Walsh et al 2012). The paucity of research on the participation of older people ageing in a rural context has been widely asserted in the literature (Keating et al 2011, Burholt & Dobbs 2012, Bacsu et al 2014.…”
Section: Introductionmentioning
confidence: 99%
“…Because the provision of public transport in rural areas is often inadequate for older people (Heenan 2010;Walsh et al 2012;Shergold, Pankhurst, and Musselwhite 2012;Wenger 2001), having a car can be crucial to remain mobile (O'Connor et al 2013), access services such as shops and GP practices, and to maintain social contacts (Walsh and Ward 2013;Scharf and Bartlam 2008;Bauer, Rottunda, and Adler 2003). Consequently, having no access to a car is often linked to social exclusion and isolation of older people (McDonagh 2006;Walsh and Ward 2013;Shergold, Pankhurst, and Musselwhite 2012;C.…”
Section: Introductionmentioning
confidence: 99%